Peran Orang Tua Migran Dalam Menanamkan Nilai Religius dan Cinta Tanah Air Kepada Anak Usia 3-8 tahun di Kampung Pandan, Malaysia - Prajnidita Zaeny Rahmalah; Labib Sajawandi (Universitas Syiah Kuala, 2023)
Indonesian character is an important thing to be instilled from an early age, through the role of parents who become the first school for children. Of the many characters, religious attitudes and love for the motherland are two things that are easily visible from human behavior. The role of parents becomes important when they live outside Indonesia, for how to instill this attitude in children. So that the love for the motherland is maintained, and the good character of children is supported by the religiosity. These two things become a benchmark for how parents, especially in Kampung Pandan, Malaysia, instill two Indonesian characters in their children. Through the method of interviews and field studies, researchers try to see the role of parents and what kind of influence it has on their children. So it is hoped that parents, even though they have busy lives as migrant workers, can still provide planting to strengthen religious attitudes and love for the motherland. Keywords: Religious attitudes, love the motherland, the role of parents, migrant workers.